COMPUTER TEACHING PROGRAMS AVAILABLE IN THE LEARNING LANGUAGE. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This article presents a comprehensive review of computer teaching programs specifically tailored to facilitate language learning within the context of the learner's native or target language. It explores the diverse range of such programs, analyzing their methodologies, features, and effectiveness in enhancing language acquisition. Additionally, the article discusses the integration of these programs into formal education settings and self-directed learning environments, highlighting their potential to supplement traditional language instruction and promote autonomous learning. By synthesizing current research findings and practical insights, this paper offers valuable guidance for educators, learners, and developers interested in harnessing the power of technology for language education.